What factors lead companies to release intellectual capital disclosure? Evidence from Indonesian manufacturers - Nila Firdausi Nuzula; Sri Mangesti Rahayu; Asih Marini Wulandari (Cogent Business & Management, 2023)
The study examined the impact of firm size and ownership structure on the comprehensiveness of intellectual capital disclosures (ICDs) using manufacturer companies listed on the Indonesia Stock Exchange during 2014-2021. The article applied partial least squares and found that firm size and ownership structure are significant in creating ICDs; however, the directions are negative. The availability of resources to create and issue more information about ICDs varies. The study also found that institutional shareholders that dominate the ownership structure could not take their potential role to supervise and encourage managers to improve ICDs. Next, the result shows that Indonesian-listed manufacturing companies rely more on short-term debt. Consequently, Leverage does not affect ICDs since the debt lenders have less intention to interfere with the managers' performance in managing and reporting annual ICDs.
Keywords: 650; capital and ownership structure; corporate governance; institutional investors; intellectual capital disclosure